THE DEFINITION OF SWITCHING TRACTION MOTORS QUALITY - Bezruchenko, V. M.; Shapovalov, A. V. (Science and Transport Progress, 2007)
Influence of the change air clearance under additional pole on position of the centerline of the area of without sparks work are shown in article. The way of the forecasting of the position to centerline of the zone безіскрової work depending on deflections geometric parameter magnetic chain additional pole are offered.